INTERACTION BETWEEN PEDAGOGUE AND CHILD TO PROMOTE PLANNING SKILLS - Priede, Ligita; Vigule, Dagnija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The goal of the pre-school competence-based education lies in the promotion of all areas of development – physical, social, emotional and cognitive, as well as helping children to acquire core competencies, including the ability to plan own activities. The research aims at theoretical and empirical study of opportunity to promote planning skills within interaction between child and pedagogue.When dealing with both daily and teacher-created problem situations, children are involved in decision-making, are trusted to be co-responsible for the decision made. By working together with an adult, child acquires planning skills, ability to achieve the goal set. To reveal the pedagogical problem of the research in full, it is also important to look at it from the point of view of a preschool teacher. To find out opinion of pre-school pedagogues, surveying was conducted; it was aimed at studying principles of child development and upbringing taken into account in practice when organizing pedagogical process promoting planning skills of pre-schoolers. The experience of pre-school teachers was analysed by frequency and interpretation using descriptive and analytical statistics method (IBM SPSS Statistika-v19.0).